Mental Health and Adjustment Problem among Adolescent School Girl - Hilda D’Souza, Metilda; Tripati, Nishi; Shilpa (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This study aims to examine the associations between positive thinking, home health social emotional adjustment, and the psychological well-being of urban and rural girls. It investigates the moderating role of positive thinking in the effects of poor school adjustment on stress and well-being. The study is conducted on 120 students of VII to XII standard randomly selected from 7 schools of sultanpur District .To assess the adjustment problem of adolescent school girls checklist was used prepared by R.K Ojha of bell’s adjustment inventory and a Nagpal and Sen Wellbeing scale was used to assess the level of subjective wellbeing.